Commanding Utterances Used In The Noble Qur'an Chapter Ta-Ha: A Pragmatic Perspective - Tafsir, Muhammad; , Dr. Maryadi, M.A (2017)
ABSTRACT Muhammad Tafsir. A320130236. COMMANDING UTTERANCES USED IN THE NOBLE QUR'AN CHAPTER TA-HA: A PRAGMATIC PERSPECTIVE. Research Paper. Muhammadiyah University of Surakarta. 2017. This research is aimed (1) at identifying the Pragmalinguistics of commanding utterances used in the Noble Qur'an Chapter Ta-Ha, (2) at describing the implicature of commanding utterances used in the Noble Qur'an Chapter Ta-Ha, (3) at describing the maxim violation of commanding utterances used in the Noble Qur'an Chapter Ta-Ha. The type of this research uses descriptive qualitative. The data source of this research is taken from Noble Qur'an Chapter Ta-Ha. The data of this research is verses of Chapter Ta-Ha that is included commanding utterance. The researcher collects data with observation and documentation. As the result, The researcher finds (1) Declarative Sentence (4%), and Imperative Sentence (96%). The most pragmalinguistics based on type of sentence that is used in this research is Imperative Sentence (96%). The researcher finds (2) generalized conversational implicature (43%), and particularized conversational implicature (57%). The most implicature type that is used in this research is particularized conversational implicature (57%). The researcher also finds (3) violation of relevance (71%), and violation of manner (29%). The most maxim violation type that is used in this research is violation of relevance (71%). Keywords: commanding utterance, pragmaliguistics, implicature.